Production line production planning model of iron and steel enterprise - Jiang, G.; He, E.; Li, G.; Kong, J.; Xie, L. (Journal of Digital Information Management, 2013)
At present, iron and steel enterprise develops towards the direction with many procedure, many process, many variety and many specification, and reaches hundreds and thousands of product series and product mix, how to plan, organize and control steel production, production schedule of its product line are key issues. According to the main characteristics of production line of iron and steel enterprise, how to make aggregate production planning of iron and steel enterprise are analyzed. An aggregate production plan model of product line of iron and steel enterprise is proposed, which is calculated by using standard library function of the Matlab7.0 genetic algorithm toolbox to program. Penalty function was adopted in the course of getting solution. These parameters of scale of father population, crossover probability, mutation probability and penalty factor were combined and optimized. The result obtained is in accordance with the actual conditions of this enterprise basically that the optimization solution to production plans of real iron and steel enterprise by using the algorithm.
Keywords: Aggregate production plan model; Genetic Algorithm; Index terms -iron and steel enterprise; MATLAB; Production line

Structure optimization of ladle bottom based on finite element method - Li, G.; Li, Z.; Kong, J.; Jiang, G.; Xie, L. (Journal of Digital Information Management, 2013)
Ladle is an important container in metallurgy industry, and its lifetime is very important for the natural production of enterprise. The stand or fall of refractory lining of ladle decides its lifetime, yet thermal stress is the direct reason of causing refractory lining breakage. In this paper the structure of ladle mainly by changing the structure of bottom with finite element method is designed, and three scheme models are put forward. By analyzing and comparing stress field of the three ladle models, finally an optimization scheme is put forward. The experiment results indicate that the lifetime of ladle gains obvious increasement, and the rationality and practicability of the scheme have been proved. The method is feasible to improve ladle's lifetime.
Keywords: Equivalent stress; Finite element method; Ladle bottom; Stress field; Structure optimization